Design, modeling and simulation of a high power factor rectifier based on the flyback converter [microfilm] - Lim, Pei Yi (Skudai : Universiti Teknologi Malaysia, 2002)
Project Paper (Bachelor of Electrical Engineering) - Universiti Teknologi Malaysia, 2002